KINERJA BADAN PERMUSYAWARATAN DESA DALAM PENYELENGGARAN PEMERINTAHAN DESA DI DESA SAING RAMBI KECAMATAN SAMBAS KABUPATEN SAMBAS - Ledo indo NIM. E1031141039; Yulius Yohanes *; Bima sujendra * (FISIP Universitas Tanjungpura Pontianak, 2019)
The writing of this thesis was based on the identification of a phenomenon tha occurs related to the Peformance of the Village Consultative Body in the administration of the Village Government in Saing Rambi Village Sambas Subdistrict Sambas Regency. This research is intended to describe and study and analyze the Performance of the Village Consultative Body (BPD) in carrying out its duties and functions in channeling the aspirations of the community, namely in making and drafting Village Regulations. This title of this thesis was appointed based on problems regarding the performance of the BPD which were considered less than opimal in channeling the aspirations of the community in making Village Regulations, because there were no Village Regulations made by the BPD other than the Code of Conduct for the BPD Itself. As well as the aspirations of rural communities that were not followed up by the BPD. This research used descriptive research with qualitative research methods. Data were collected using observation, interview and documentation techniques. The research was carried out at Saing Rambi Village Sambas Subdistrict, Sambas Regency. The indicators used to measure the performance of the BPD are Responsiveness, Responsibility and Accountability according to Moeheriono. The conclusion in this study is that the Village Consultative Body (BPD) has not been maximized in carrying out its duties and functions due to a lack of understanding of its tasks and functions as well as a lack of understanding in the mechanism of Village Regulation Formulation so that the BPD has not been maximized in channeling community aspirations in the form of Village Regulations. Keywords : BPD Performance, Village Regulations, Communiy Aspirations.